(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
In this article, the level of occurrence of algocenoses in the plains of the northern, southern, eastern and western parts of the Fergana Valley, the abundance of Cyanophyta species, the level of salinity in irrigated soils, mobile phosphorus, exchangeable potassium, NSO3, SL, Sa, Mg, SO4, Na+K and humus in the soil amount, types of soil, climate and specific nature are considered.